PATH-27. CLINICAL, RADIOLOGIC AND PROGNOSTIC PROFILE OF IDH WILD TYPE DIFFUSE ASTROCYTOMA WITH MOLECULAR FEATURES OF GLIOBLASTOMA. (9th November 2020) - Akintola, Oluwatosin; Samore, Wesley; Alvarez, Maria Martinez-Lage; Gerstner, Elizabeth
Abstract: BACKGROUND: cIMPACT-NOW-3 recommends that IDH-wildtype diffuse astrocytic glioma Grade II or III with EGFR amplification, or combined whole chromosome 7 gain and whole chromosome 10 loss, or TERT promoter mutation should receive an integrated classification: Diffuse astrocytic glioma, IDH-wildtype with molecular features of glioblastoma, WHO grade IV. The aims of this study were: Outline the features of a cohort of patients with molecular glioblastoma according to the above criteria; Assess clinical and molecular factors that may inform prognosis; Determine if cIMPACT-NOW-3 recommendation changed clinical practice and clinical trial enrolment. METHODS: 61 patients diagnosed with IDH-wildtype diffuse astrocytic glioma Grade II or III and EGFR amp or mTERT or chromosome (+7/-10) between 2011 and 2019 at MGH were included in this single center retrospective cohort study. Data collected: sex, age, extent of surgery, functional status, histological grade, molecular diagnostics and treatment. Progression was defined using RANO criteria, progression was quantified in terms of months from the initial surgery. Survival was defined in terms of months from initial surgery to date of death or last known visit. RESULTS: mOS was 16 months, mPFS was 9 months. 14 patients (23%) survived > 24 months, 7 ≥ 36 months (mOS 32 months; 9 deceased). The probability of survival in patients with markedly enhancing tumors was 0.5 at 3 months versus 0.5 at 11 months in non-enhancing tumors. The probability of survival in patients who underwent biopsy only was 0.5 at 5 months compared to 0.5 at 12 months in patients with maximally resected tumors. 1 patient was enrolled in a clinical trial at diagnosis. 6 were enrolled at time of recurrence. CONCLUSIONS: mOS and pFS in the deceased patients was comparable to historical data on survival in IDH wild-type glioblastomas. Inclusion criteria in clinical trials have not reflected the cIMPACT-NOW-3 recommendation so far.